2022
DOI: 10.1111/gcb.16484
|View full text |Cite
|
Sign up to set email alerts
|

Plant secondary metabolic responses to global climate change: A meta‐analysis in medicinal and aromatic plants

Abstract: Over the past century, global climate changes caused by human activity and in particular industrial development are posing an extreme and irreversible threat to the entire terrestrial ecosystem. Most recently, the urgency of climate change was further emphasized by over 10,000 world scientists due to the increased frequency of accompanying climate disasters such as devastating flooding,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 466 publications
(181 reference statements)
0
8
0
Order By: Relevance
“…In addition to N fertilization, climatic factors, especially annual temperature and precipitation, were emphasized as the key drivers shaping rice NUtE variations (Figures 2 and 3; Figure S6). Supportively, temperature and precipitation have been ecologically and evolutionally identified as major determinants of plant traits at a global scale (Moles et al, 2014), which has been demonstrated in the responses of plant photosynthesis (Liang et al, 2020), secondary metabolism (Sun et al, 2023), and nutrient resorption (Yuan & Chen, 2009). A more recent meta‐analysis also stressed the effects of climate factors, especially temperature, on the N fertilizer use efficiency in different crops (Yu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to N fertilization, climatic factors, especially annual temperature and precipitation, were emphasized as the key drivers shaping rice NUtE variations (Figures 2 and 3; Figure S6). Supportively, temperature and precipitation have been ecologically and evolutionally identified as major determinants of plant traits at a global scale (Moles et al, 2014), which has been demonstrated in the responses of plant photosynthesis (Liang et al, 2020), secondary metabolism (Sun et al, 2023), and nutrient resorption (Yuan & Chen, 2009). A more recent meta‐analysis also stressed the effects of climate factors, especially temperature, on the N fertilizer use efficiency in different crops (Yu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Secondary metabolites in higher plants play indispensable roles in counteracting salinity stress partially through regulating osmotic adjustment (Batista‐Silva et al, 2019; Chiappero et al, 2021) and ROS homeostasis (Chan et al, 2012; Sun et al, 2022). It has been shown that the activation of phenylpropanoid, a vital secondary metabolic pathway, plays a dominant role in resisting salinity stress (Calzone et al, 2023; Cao et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the results showed that phenolic compounds changed across annual cycles as part of the modifications in the metabolic biosynthesis and accumulation of this compound in the roots of E. montanum . In this sense, through a meta-analysis, Sun et al [ 25 ] determined that increases in temperatures and decreases in annual rainfall increase the levels of phenolic compounds in medicinal and aromatic plants.…”
Section: Discussionmentioning
confidence: 99%